Scratch Technique for Alternative Batik Product Creation - Widodo, Suryo Tri; Wardoyo, Sugeng (Institut Seni Indonesia Yogyakarta, 2023)
This article is motivated by the fact that so far the use of equipment for written batik has only relied on written canthing equipment which is commonly used by most batik artisans. Thus, it is deemed necessary to develop alternative equipment outside of written canthing. The offer of written batik equipment outside of this written canthing is the use of equipment in the form of a fruit knife which is designed and modified in such a way that it can be used for scratching techniques. The use of this tool is considered appropriate to be applied to batik products, because in addition to having a high selling value or economic value, it can also provide alternative tools other than written canthing, because the level of batik production is also required to be faster. This breakthrough or positive innovation from the use of batik tools for the scratch technique is quite important, considering the need for batik products is also increasing.